A clinical audit and confidential enquiry of caesarean section indications at rural tertiary health care centre - Thool, Ketki N.; Jain, Shuchi M.; Shivkumar, Poonam V.; Jain, Manish A.; Podder, Manjiri R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Worldwide CSR has been steadily increasing beyond recommended level of 15 %by WHO. High CSR have been reported in developed and developing countries. Reasons for increase in CSR are not obvious and somewhat complex. Thus, present study was undertaken to analyze various indications for CS performed at rural tertiary health care centre Sewagram, M.S. Methods: This was prospective study included all women who underwent CS from 1st January 2015 till 30th June 2016. Data was entered in MS excel sheet analyzed with percentage and chi square test using SPSS ver.17. Results: CSR was 36 .88% in present study. As per NICE guidelines CS were classified in four categories based on urgency, women were distributed in each category. Category I had 22.62%, category II -38.61%, category III - 28.37% and Category IV - 10.40% women. In CAT I common indication was foetal bradycardia (71.53%). In CAT II CS, common indication was non reassuring foetal status (38.82%). Breech presentation (14.74%) and previous scar with doubtfull scar integrity (14.33) were next common indications. In CAT III (43.43%), IV (41.13%) previous LSCS with inadequate pelvis was the common indication. Confidential enquiry revealed that 26.17% (28/107), 20.3% (40/197), 23.17%, (35/151) and 8.3 % (5/60) of CAT I, II, III and IV CS had questionable indications. Conclusions: In this study, CSR was higher than WHO standard. Common indications in primipara was foetal distress while in multiparas primary indication previous LSCS